LHCspin: A polarized internal target for the LHC - Lenisa, Paolo; Steffens, Erhard; Carassiti, Vito; Ciullo, Giuseppe; Di Nezza, Pasquale; Pappalardo, Luciano Libero; Vasilyev, Alexander (Proceedings of Science, 2019)
The LHCspin project aims to bring both unpolarized and polarized physics at the LHC through the installation of a gaseous fixed target at the upstream end of the LHCb detector. The forward geometry of the LHCb spectrometer (2 < η < 5) is perfectly suited for the reconstruction of particles produced in fixed-target collisions. The fixed-target configuration, with center-of-mass energies ranging from √sNN = 72 GeV in collisions with Pb beams to √s = 115 GeV in pp interactions, allows to cover a wide backward center-of-mass rapidity region, corresponding to the poorly explored high x-Bjorken and high x-Feynman regimes. The use of transversely polarized H and D targets will allow to study the quarks TMDs in p-p collisions at unique kinematic conditions. Furthermore, being LHCb specifically designed for heavy-flavor physics, final states with c- or b-quarks (e.g. inclusive quarkonia production) will be efficiently reconstructed, thus providing, among other fundamental measurememnts, access to the so-far unknown gluons TMDs. The contribution focuses on the design considerations of the polarized internal target and on a discussion of possible critical machine issues.
CRIS-Team Scopus Importer:2024-12-16